2005
DOI: 10.1097/01.ccm.0000155923.97849.6d
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillatory ventilation: Lessons from the neonatal/pediatric experience

Abstract: Efforts to minimize ventilator-induced lung injury in adults with hypoxemic respiratory failure have recently focused on the potential role of high-frequency oscillatory ventilation (HFOV). However, HFOV has been studied in newborns with hypoxemic respiratory failure for nearly 3 decades. In this brief review, we attempt to summarize key physiological principles learned from this cumulative neonatal/pediatric experience with HFOV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 48 publications
2
48
0
6
Order By: Relevance
“…42,43 HFOV uses an oscillatory pump to deliver active inspiration and expiration, producing pressure oscillations around a relatively constant P aw . It delivers very low V T at high breathing frequencies and is designed to recruit and maintain adequate end-expiratory lung volumes, attenuate atelectrauma, and improve oxygenation.…”
Section: High-frequency Oscillatory Ventilation Basic Principlesmentioning
confidence: 99%
“…42,43 HFOV uses an oscillatory pump to deliver active inspiration and expiration, producing pressure oscillations around a relatively constant P aw . It delivers very low V T at high breathing frequencies and is designed to recruit and maintain adequate end-expiratory lung volumes, attenuate atelectrauma, and improve oxygenation.…”
Section: High-frequency Oscillatory Ventilation Basic Principlesmentioning
confidence: 99%
“…In adult patients with ALI, reviews by leading experts in the field and a Cochrane systematic review of RCTs found that HFOV during the early phase of ALI seems to have no benefits and that there might be a role for HFOV only in severe ARDS [99][100][101].…”
Section: High-frequency Oscillatory Ventilationmentioning
confidence: 99%
“…Therefore, one might expect that with HFOV important goals of lung protective ventilation (preventing physical injury due to repetitive closure and re-opening of alveoli) may be achieved. Most of the clinical HFOV studies were conducted in newborns with neonatal RDS; however, no clear benefit on mortality compared with conventional ventilation (CV) was observed [95][96][97][98][99].…”
Section: High-frequency Oscillatory Ventilationmentioning
confidence: 99%
“…28 Another lung-recruitment option is HFOV with incremental increases in mean airway pressure to achieve the desired oxygen saturation or lung inflation on chest radiograph. 29 Goldman et al used HFOV to facilitate lung recruitment after repair of long-segment congenital tracheal stenosis, 18 and HFOV appeared to be beneficial during ECMO.…”
Section: Discussionmentioning
confidence: 99%